2022
DOI: 10.3390/molecules27185959
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Storage Regimes on the Levels of Physicochemical Characteristics, Especially Free Acidity in Talh (Acacia gerrardii Benth.) Honey

Abstract: This study investigates how storage conditions (temperature and duration) may affect the physicochemical parameters, especially free acidity (FA), of Talh honey originating from Acacia gerrardii that have naturally high FA levels. Fresh Talh honey samples were kept at 0, 25, 35, and 45 °C, and analyzed monthly over a period of eight months. The Talh honey was monofloral with 69% A. gerrardii pollen content. The free acidity (FA) of freshly harvested Talh honey samples was higher (93 ± 0.3 meq/kg) than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Storage temperature was found to be a factor with the highest significant influencing power on the FA (p < 0.05). Although all the values of FA in this study were beyond the standard limit, the results indicated that the stability of the FA of Talh honey was maintained stable at low temperatures (0-25 • C) for up to 6 months without significant effects [194]. In this study, statistical analysis showed the FA to exert a positive correlation with storage period (0.401), storage temperature (0.631), 5-HMF (0.852), color (0.541), moisture (0.440) and EC (0.155).…”
Section: Free Aciditymentioning
confidence: 53%
See 4 more Smart Citations
“…Storage temperature was found to be a factor with the highest significant influencing power on the FA (p < 0.05). Although all the values of FA in this study were beyond the standard limit, the results indicated that the stability of the FA of Talh honey was maintained stable at low temperatures (0-25 • C) for up to 6 months without significant effects [194]. In this study, statistical analysis showed the FA to exert a positive correlation with storage period (0.401), storage temperature (0.631), 5-HMF (0.852), color (0.541), moisture (0.440) and EC (0.155).…”
Section: Free Aciditymentioning
confidence: 53%
“…Reported studies for Tahl honey, which by its nature has FA values exceeding international limits, recorded a high decrease in saccharide concentrations especially for samples stored at 35 and 45 • C for different time intervals up to eight months at 0, 25, 35 and 45 • C [194]. Under all the storage temperatures, the sugars (fructose, glucose and sucrose) significantly decreased during the storage period with reducing sugars' amounts to reach levels below legislation limits (Fructose + Glucose >60 g/100 g) [96].…”
Section: Sugarsmentioning
confidence: 92%
See 3 more Smart Citations